PEMANFAATAN LIMBAH MINYAK BEKAS PENGGORENGAN TAHU SEBAGAI BAHAN DASAR PEMBUATAN BIODIESEL - De Budi Irwan Taufik (Institut Pendidikan Indonesia IPI Garut, 2019)
AbstractThis research is entitled “Utilization of “tofu/ soybean curd” used oil waste as a basic of biodiesel making”. This research aims to “Find out whether the used frying oil can be used as a base for biodiesel, and how is the quality of the biodiesel produced?